Методика перекладу фахових текстів студентами медичних ВНЗ на заняттях з дисципліни «Українська мова (за професійним спрямуванням) - Козиряцька, Світлана Анатоліївна; Kozyryatska, Svetlana; Козыряцкая, С. А. (My University, 2015)
У статті розглянуто основні аспекти перекладу фахових текстів студентами медичних вузів на заняттях з «Української мови (за професійним спрямуванням)» та запропоновано методику такої роботи. The article deals with the basic aspects of translation of professional texts by medical students in the classroom of the discipline “Ukrainian language (for professional purposes) ” and the methods of such work are proposed. Language training of students in the classroom of the discipline “Ukrainian language (for professional purposes) ” should be aimed at the systematic assimilation of important components of professional speech, cognitive, communicative and expressive. Successful mastering of the first two can be provided by a work with professional texts, including their translation. In the article are proposed the methods of work with the professional texts during their translation by the medical students: 1) the first reading that will provide awareness of the general meaning of the text; 2) re-reading - to understand the importance of highly specialized words that are hard to translate (to emphasize the role of context); 3) using of terminology dictionaries, orientation materials and media for the translation of the simplest concepts; 4) use of explanatory or encyclopedic dictionaries, work with dictionary articles which allow you to become familiar with the examples of word usage, to find the synonyms to chosen words, and to get acquainted with the lists of literature to the dictionary to be aware of new and special edition; 5) memorizing common translation structures; attention to the speech patterns, with different translation depending on the content (including the functional parts of speech). В статье рассмотрены основне аспекты перевода специализированных текстов студентами медицинских вузов на занятиях по “Украинскому языку (профессионального направления)” и предложена методика такой работы.
Methods of translation of specialized text by students of the medical Universities on the lessons of "Ukrainian language (professional purposes)"
Методика перевода специализированных текстов студентами медицинских вузов на занятиях по дисциплине “Украинский язык (профессионального направления)”
Keywords: фахові тексти; контекст; мовні конструкції; медична термінологія; специализированные тексты; языковые конструкции; медицинская терминология; Specialized texts; context; language models; medical terminology